Political Uncertainty and Financial Market Uncertainty in an Australian context - Smales, Lee (Elsevier BV * North-Holland, 2014)
This paper seeks to investigate the influence of political uncertainty, surrounding the Australian federal election cycle, on financial market uncertainty. Measures of political uncertainty are constructed and their relationship with market uncertainty, as measured by implied volatility, explored. Empirical evidence suggests that increasing (decreasing) levels of uncertainty around the election induce higher (lower) levels of market uncertainty. An increasing likelihood of the incumbent party, whose economic policies are presumably well-known, winning the election, reduces market uncertainty. This relationship is stronger when political uncertainty is highest, when the business cycle contracting, and when the level of economic risk is high. Higher levels of political uncertainty tend to be associated with declining levels of outstanding debt, and lower issuance of long-term Government debt, driven by falling demand and higher yields.